COVID-19 and the Sustainable Development Goals: Future Vision for Childhood (Journal of the College of Education for Women, 2025)
The New Development Goals Report 2021 and United Nations sources indicated the result of the Covid-19 injury, and that 101 children are below the level of reading proficiency, which may change the gains achieved over two decades in the field of education, which led to the research of a scientific problem as a research text "What is the great vision of the future of childhood in light of the repercussions of Covid-19, and the development goals (2016/2030)"; Research in describing the Corona virus 19 towards achieving comprehensive development goals, and commitment to comprehensive development goals in the field of childhood, and inductive models were used through a desk survey of the literature on the Covid-19 virus and its association with global development goals in the field of technology as a model, during the time period (2020 - 2021 AD). The research reached a set of results as starting points for the forward-looking vision for the future of childhood the repercussions of the Covid-19 & the Sustainable Development Goals. That the forward-looking vision for the future of childhood be launched in the repercussions of the Covid-19 and the Sustainable Development Goals. To focus on the goal of a forward-looking vision for the future of childhood. To beginning the vision for childhood on the literature and the theoretical framework and the presentation and analysis of the research heritage through {the rules that social workers (academics and practitioners) can rely on - indicators for developing the forward-looking vision.